Basic and Clinical Aspects of Interferon Gamma - Prakash, Hridayesh (IntechOpen, 2022)
This book discusses the significance of interferon (INF) in the clinical aspects of the disease. Chapters address the biological, chemical, and physiological aspects of IFN and how IFN can assist various targeted health interventions. The information contained herein is useful for designing IFN gamma-directed strategies for managing various diseases discussed in the text.